PENGEMBANGAN GAME EDUKASI PADA MATA PELAJARAN KOMPUTER GRAFIS KELAS XI DKV DI SMK NEGERI 4 SUNGAI PENUH - Aidil Fitra Hadi; Haris Kurniawan; Herisvan Hendra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of students in the Computer Graphics class XI DKV at SMK Negeri 4 Sungai Penuh. The lack of variety in learning media and low student motivation in understanding computer graphics theory were the main problems identified. The purpose of this study was to develop educational game learning media for the Computer Graphics class XI DKV at SMK Negeri 4 Sungai Penuh and to determine the level of validity and practicality of this educational game learning media for the Computer Graphics class XI DKV at SMK Negeri 4 Sungai Penuh. The method used was Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The product developed was the educational game